2018
DOI: 10.3390/catal8070273
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Electrocatalytic Carboxylation of 1-Phenylethyl Chloride at Cu Foam Cathode

Abstract: A simple and efficient electrocatalytic carboxylation of benzyl chloride with CO 2 is described. The reaction operates under 1 atm CO 2 and room temperature in a single chamber electrolysis cell with Cu foam cathode and Mg sacrificial anode. No additional catalyst is needed, and noble metal is not necessary. The effects of cathode material, solvent current density, charge amount, and temperature were studied using 1-phenylethyl chloride as a model compound. Under optimal conditions, 99% yield of 2-phenylpropio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Combined yields and Faradaic efficiencies (FEs) of RCO 2 – and RCO 2 R (EC products) represent EC selectivity in the electrolysis. Other products of electrochemical nature , included dimer R–R, alcohol R–OH, ether R–O–R, and alkylarene R–H. Other side products, such as alkenes and their oligomers, ,, can be formed as a result of nonelectrochemical transformations of reactive intermediates produced during electrolysis and are not included in Figure (for detailed analysis of the formation of minor products, see the Detailed Reaction Mechanism below and Table S1 and Figure S4, SI).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Combined yields and Faradaic efficiencies (FEs) of RCO 2 – and RCO 2 R (EC products) represent EC selectivity in the electrolysis. Other products of electrochemical nature , included dimer R–R, alcohol R–OH, ether R–O–R, and alkylarene R–H. Other side products, such as alkenes and their oligomers, ,, can be formed as a result of nonelectrochemical transformations of reactive intermediates produced during electrolysis and are not included in Figure (for detailed analysis of the formation of minor products, see the Detailed Reaction Mechanism below and Table S1 and Figure S4, SI).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, electrocarboxylation (EC) of organic halides (R–X) has attracted attention as a green alternative for the synthesis of nonsteroidal anti-inflammatory drugs, such as ibuprofen, and important precursors in industrial processes, such as cyanoacetic acid, an, , and many others. , It has been shown that EC of organohalides with different cathodes (e.g., Ag, Cu, and Ni) in undivided cells with sacrificial Mg or Al anodes generally results in the formation of corresponding carboxylic acids with moderate to high yields in the form of magnesium (or aluminum) salts. Although the formation of these salts simplifies the work-up procedure, it negatively affects the reaction atom economy due to the anode consumption in the course of reaction. Formation of insoluble products in EC reactions also causes electrode passivation, resulting in large current fluctuations (potentiostatic electrolysis) or increase in the cell voltage (constant current electrolysis) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 24 , 108 There is precedent for electroreductive cross-coupling of organohalides with CO 2 . 104d , 109 Lu and Wang reported an enantioselective electrochemical carboxylation, utilizing chiral cobalt salen complexes ( Scheme 13 A). This example illustrated the possibility of an asymmetric electroreductive carboxylation of inexpensive and optically inactive alkyl chloride 62 for the first time.…”
Section: Electrochemical Reduction For Unique Chemoselectivities and mentioning
confidence: 99%